Insurance as a Form of Risk Transfers of Local Government Units - Hajdys, Dagmara; Wieteska, Stanisław (Journal of Finance and Financial Law, 2021)
The aim of the study is to identify risks characteristic of the local government sector and to present the insurance offer dedicated to this sector on the example of the city of Łódź. The article puts a thesis forward that a comprehensively structured insurance offer contributes to the optimal transfer of local government risks. The study was based on a literature review, legal acts and an insurance offer addressed to local government units. A properly conducted risk identification process and the insurer selection procedure lead not only to the selection of the optimal insurance offer, but also to the entity itself. A limited analysis of the example of the city of Łódź shows that local government authorities are interested in comprehensive, "tailor-made" insurance policies offered by one insurer. This translates into the time of acceptance, consideration of the damage and payment of compensation. Insurance programs directly addressed to local government units that appear on the insurance market should be assessed positively. An example is the "Safe Commune" program. It should be expected that in the coming years, due to the special budget constraints resulting from the Covid-19 pandemic, the interest of local authorities will increase in new, innovative solutions in the field of risk insurance.